Religious Networked Publics: Seeking Authenticity By Digital Means - Golan, Oren; Evolvi, Giulia; Martini, Michele; Scott, Sasha; Vaisman, Carmel (AoIR Selected Papers of Internet Research, 2017)
Recently, users and religious entrepreneurs are expanding the meaning of authentic experiences of faith to the digital realm. These innovators are challenging well-established forms of representation and authority for believers. Given these developments, we ask: how is the authentic relation to the divine negotiated by users through their engagement with digital technologies? Drawing on Boyd (2010) and Papacharissi (2014), this panel proposes that collective faith-based use of social networking sites (SNSs) can construct what we deem as a “religious networked public”. We contend that this public formation advances an online sense of imagined belonging by users, as well as restructures existent religious communities through socio-technological affordances. In this panel, we aim to present current data on ways of approaching traditional and established religious practices (i.e Hijaab head coverings, Catholic confession, Pilgrimage) as they are reorganized on internet tracts. Through this newly advanced framework, we offer an opportunity to reflect on past theoretical concepts (i.e. “online religious communities”, “mediatization”, “e-religion”, “third spaces”), and elucidate key concepts in the sociology of (online) religion such as authenticity, religious identity and authority.